Book Review: Dressing Prehistory (Oblekani Praveku) by K. Urbanová and J. T. Pulpán - Helena Březinová (EXARC, 2018)
A unique popular education publication called Oblékání pravěku (Dressing prehistory) has appeared on the Czech book market. It is a work by archaeologist Kristýna Urbanová, and Jan T. Půlpán, an experienced experimenter. At first glance the book attracts attention with an unusually large format, well chosen because of the foundation elements of the publication – colour photographs of prehistoric clothes reconstructions.